Freshwater stingrays: study of epidemiologic, clinic and therapeutic aspects based on 84 envenomings in humans and some enzymatic activities of the venom - Haddad, V; Neto, D. G.; de Paula Neto, J. B.; de Luna Marques, F. P.; Carbaro, K. C. (Elsevier B.V., 2004)
Freshwater stingrays are very common in the Parana, Paraguay, Araguaia, and Tocantins Rivers and tributaries in Brazil. This study presents the clinical aspects of 84 patients injured by freshwater stingrays. Intense pain was the most conspicuous symptom. Skin necrosis was observed in a high percentage of the victims, mostly fishermen and bathers. The initial therapeutic procedures, like immersion of the affected member in hot water were effective in the initial phases of the envenoming, especially in the control of the acute pain; however, they did not prevent skin necrosis. By SDS-PAGE, the freshwater stingray (Potamotrygon falkneri) venom extract presented a major band of approximately 12 kDa. Several other components distributed between 15 and 130 kDa were detected in the venom extract. Many components with molecular mass above 80 and 100 kDa have gelatinolytic and caseinolytic activities, respectively. Hyaluronidase activity was detected only in a component around 84 kDa in P. falkneri venom extract. Our results demonstrated that the presence of these enzymes could explain partially the local clinical pictures presented by patients wounded by freshwater stingray. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: venomous fishes; freshwater stingrays; stingrays; potamotrygonidae; Potamotrygon; injuries by stingrays; necrosis; venom